Bilateral Cerebrovascular Stroke as an Initial Presenting Symptom of Moyamoya Disease - Ester Ilyayeva; Khaled Nada; Roxane Farahi Far; Kamal Albright; Manmeet Kaur Gujral; Menachem Gold (Case Reports in Critical Care)
Moyamoya disease is a rare condition affecting the circle of Willis and its branching arteries. While the pathogenesis is unclear, it causes progressive occlusion of multiple cerebral vessels leading to severe strokes. We report a case of a 47-year-old Hispanic woman with HTN presented with altered mental status and bilateral upper and lower extremity weakness with dystonic-like upper extremity movement. Serial brain CTs and angiography were performed which showed massive frontal and parietal cerebral infarcts with radiological evidence of moyamoya disease.